New Teaching And Learning Methods For The Post-Pandemic Time - Raykova, Zhelyazka; Raganova, Janka; Yıldızhan, Hasan; Stoyanova, Diana; Tsokov, Galin; Stoyanov, Stefan; Hruska, Martin; Spodnıakova Pfefferova, Miriam; Petrışor, Iulian; Bulıgıu, Lon; Constantin Sararu, Silviu; Marıus Etegan, Cristian; et al. (Academician Publishing Book DOI Portal, 2023)
-